The relationship between fetal environment and menopausal age: A narrative review study - Marzie Reisi; Leila Asadi (Mashhad University of Medical Sciences, 2021)
Introduction: When the follicle reserve, which is developed solely during the fetal period, is depleted, women enter menopause. Adverse uterine conditions can affect the ovarian follicles and thus the age of menopause. Considering the widespread consequences of menopause and its effects on women's life, this review study was performed with aim to investigate the association between the fetal environment and menopausal age. Methods: In this review study, articles were searched in databases of Scopus, Science direct, Pubmed, Web of Science, Uptodate, Magiran, and SID without time limit and with English and Persian language limitations and using the keywords of menopause, birth weight, gestational age, famine. Findings were examined in 4 thematic areas (birth weight, twins, gestational age at birth and famine exposure in fetal life). Results: After revising 3100 articles, the results of 13 articles which had inclusion criteria were reviewed. None of the studies reported statistically significant association between low birth weight, gestational age and risk of famine during pregnancy with menopausal age. Two studies have reported an association between high birth weight and earlier menopausal age. Although studies of twins have shown no significant association between birth weight and menopausal age in twins, there are indications that twins with primary ovarian insufficiency experience premature menopause. Conclusion: The changes in fetal environment may be related to menopausal age. Since premature menopause leads to shorter reproductive life and increased disease in women, it is recommended that more studies be performed in this regard to investigate the effects of fetal life on menopausal age.